KEBIASAAN MAKAN DAN MUSIM PEMIJAHAN IKAN LAIS (Criptopterus sp.) DI SUAKA PERIKANAN SUNGAI SAMBUJUR, KABUPATEN HULU SUNGAI UTARA KALIMANTAN SELATAN - Dadiek Prasetyo (Jurnal Perikanan Universitas Gadjah Mada, 2005)
Study on feeding habit and spawning season of lais (Criptopterus sp.) in fisheries reserve Sungai Sambujur, Hulu Sungai Utara, South Kalimantan was conducted from June until December 2004. The objectives of  this research were to know feeding habit and spawning season of lais in fisheries reserve Sungai Sambujur. Feeding habit was analysed by index of preponderance. Somatic index maturity and fecundity were determined by Nikolsky and gravimetri metods, respectively. The results  showed that the natural feed of  lais in dry season were  43% fish fragmen, 55% insect fragmen and 2% unidentified materials. While  in wet season, the natural feed of lais were 32% fish fragmen, 67.5% insect fragmen and 0.5% unidentified materials. Somatic index maturity of lais varied monthly ranging from  I to V. Fekundities of lais  were 197-5146 with body weight ranging from 17.5 to 40 g, and egg diameters ranged from 0.6 to 0.8 mm.Study on feeding habit and spawning season of lais (Criptopterus sp.) in fisheries reserve Sungai Sambujur, Hulu Sungai Utara, South Kalimantan was conducted from June until December 2004. The objectives of  this research were to know feeding habit and spawning season of lais in fisheries reserve Sungai Sambujur. Feeding habit was analysed by index of preponderance. Somatic index maturity and fecundity were determined by Nikolsky and gravimetri metods, respectively. The results  showed that the natural feed of  lais in dry season were  43% fish fragmen, 55% insect fragmen and 2% unidentified materials. While  in wet season, the natural feed of lais were 32% fish fragmen, 67.5% insect fragmen and 0.5% unidentified materials. Somatic index maturity of lais varied monthly ranging from  I to V. Fekundities of lais  were 197-5146 with body weight ranging from 17.5 to 40 g, and egg diameters ranged from 0.6 to 0.8 mm.